Clinical utility of pulmonary artery catheter derived hemodynamic parameters: a prospective clinical study - A.K. Kolotukhin; A.Yu. Bakanov; V.S. Shabaev; R.E. Rzheutskaya; L.Z. Biktasheva; A.V. Shugurov; V.A. Mazurok (Russian Journal of Anesthesiology and Reanimatology, 2026)
Background. Induction of anesthesia and mechanical ventilation frequently lead to arterial hypotension whose nature can be elucidated through analysis of volumetric and pressure-derived hemodynamic parameters. These include measured or calculated, including indexed, indicators of the left and right cardiac chambers (left ventricular stroke work index, right ventricular stroke work index), peripheral (indexed total peripheral vascular resistance — iTPVR) and pulmonary (indexed pulmonary vascular resistance — iPVR) vascular resistance. Informative value of these indicators remains a subject of debate. Objective. To evaluate utility of pulmonary artery catheter derived hemodynamic parameters at induction of anesthesia and initiation of mechanical ventilation in patients with various heart failure phenotypes scheduled for CABG. Material and methods. We studied 100 patients with coronary artery disease at induction of anesthesia and initiation of mechanical ventilation immediately before myocardial revascularization. Group 1 (n=50) consisted of patients with preserved left ventricular ejection fraction (LVEF ≥50%); group 2 (n=50) — reduced LVEF (41–49%). Hemodynamic assessment included pressure-derived parameters (pulmonary artery catheter) and volumetric measurements (transesophageal echocardiography, TEE). Measurements were performed at four stages: (1) before induction of anesthesia (“baseline”); (2) after induction of anesthesia, prior to administration of muscle relaxants (“spontaneous breathing phase”); (3) 10 min after initiation of mechanical ventilation (“post-MV”); and (4) 3 min after Trendelenburg positioning (30° head-down tilt). Results. Anesthesia induction resulted in arterial hypotension in both groups without impairment of myocardial contractility. This indicated vasoplegia as predominant mechanism. Initiation of mechanical ventilation and subsequent Trendelenburg positioning increased central venous pressure (CVP) and pulmonary artery pressures (mean PAP) by 20% and 60%, respectively (p